Small Split Doses of CD34+ Peripheral Blood Stem Cells to Support Repeated Cycles of Nonmyeloablative Chemotherapy - Maxim Yankelevich; Sureyya Savasan; Igor Dolgopolov; Roland Chu; George Mentkevich (Case Reports in Oncological Medicine)
Cumulative myelosuppression is the main limiting factor for administration of repeated cycles of chemotherapy. We present a case series of five pediatric patients with high-risk solid malignancies who received small split peripheral blood stem cells (PBSC) doses of less than 1 × 106/kg CD34+ cells obtained after a single leukapheresis procedure and given after repeated cycles of ICE (ifosfamide, carboplatin, and etoposide) chemotherapy. Mean duration to absolute neutrophil count (ANC) recovery to >1000/mm3 and platelet recovery to >50 × 103/mm3 was 17.1 and 24.3 days. Using split doses of PBSC prevented prolonged neutropenia after repeated cycles of submyeloablative chemotherapy.